Motivational interviewing increases autopsy rates (Swiss Medical Weekly, 2018)
BACKGROUND Autopsies are a crucial source of medical knowledge. Unfortunately, autopsy rates have decreased markedly in Switzerland and many other countries. Communication between clinicians and the deceased’s sceptical relatives is crucial to obtain autopsy permission. This survey investigates the personal views of multimorbid patients and their relatives on autopsies. In addition, the study examines whether motivational interviewing of the decedent’s relatives according to Miller and Rollnick can be used to increase autopsy rates. METHODS At the Department of Medicine of the Kantonsspital Winterthur, Switzerland, the views of multimorbid patients and their relatives on autopsies were surveyed between 1 September 2014 and 31 December 2015 (14 months) using a standardised questionnaire. All physicians participated in a 1-hour tutorial on motivational interviewing. From November 2014 to October 2015, motivational interviewing was used to improve the communication between physicians and the decedent’s relatives and to obtain autopsy permission. Autopsy rates before, during and after this intervention were compared. RESULTS Questionnaires were completed by 135 multimorbid patients and 82 corresponding relatives. Views on autopsies were mostly positive. Before the intervention, there had been a steady decline in the number of autopsies ranging from 18.9% (412 deaths and 78 autopsies) in 2010, to 12.8% (489 deaths and 53 autopsies) in the 12-month period prior to the intervention. During the intervention (motivational interviewing of the decedents’ relatives in asking for autopsy permission), 489 deaths occurred and 132 autopsies were performed (26.9%). This increase was highly statistically significant (p